Effect of lithium salt on physicochemical properties of P(MMA-co-EMA) based copolymer electrolytes for dye-sensitized solar cell application - Dzulkurnain, Nurul Akmaliah; Rani, Mohd Saiful Asmal; Ahmad, Azizan; Mohamed, Nor Sabirin (Springer Verlag (Germany), 2018)
In the present work, free standing films of methyl methacrylate and ethyl methacrylate complexed with different weight ratios of lithium iodide salt were successfully prepared via solution casting technique. Fourier transform infrared spectroscopy showed that the interaction between lithium ion and oxygen atoms occurred at carbonyl and ether group of the host copolymer. The incorporation of 20 wt% lithium iodide optimized the ambient temperature conductivity of the electrolyte up to 1.3 × 10−6 S cm−1. The glass transition temperature and activation energy decreased with increase in ionic conductivity which can be explained by the increase of segmental motion in polymer matrix resulting in enhancement of ion mobility. The majority of ions in this copolymer systems were anions as confirmed from lithium transference number measurements. The dye-sensitized solar cell fabricated using the highest conducting film exhibited photovoltaic response efficiency of 0.45%.